2004
DOI: 10.1111/j.1548-2456.2004.tb00286.x
|View full text |Cite
|
Sign up to set email alerts
|

Telecommunications Reform in Mexico from a Comparative Perspective

Abstract: This paper examines the process of reform in the Mexican telecommunications sector and makes comparisons with similar processes in the United States, New Zealand, and Brazil. Differences in policy responses are explained by the structure of the political institutions and the policy context in any given country. The policy lessons to be drawn from the regulatory experiences examined are that the sequence and the pace of reform influence policy outcomes. The speed with which the Mexican reform was carried out le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 20 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…Nevertheless, for some critics of privatization, benefits are not unconditional. Instead, they depend on well-designed privatization, free of corruption, that promotes competition under conditions of clear, credible rules (Auriol and Blanc 2009; Casanueva-Reguart 2013; Li and Xu 2004;Mariscal 2004).…”
Section: Data and Empirical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, for some critics of privatization, benefits are not unconditional. Instead, they depend on well-designed privatization, free of corruption, that promotes competition under conditions of clear, credible rules (Auriol and Blanc 2009; Casanueva-Reguart 2013; Li and Xu 2004;Mariscal 2004).…”
Section: Data and Empirical Analysesmentioning
confidence: 99%
“…In addition to these effects, monopolies can take advantage of economies of scale (Varian 2005), and this could also foster greater investment to take advantage of this favorable context (Ros 1999). However, competition might also boost investment in the sector as firms employ these resources to become more efficient and try to capture greater market shares (Auriol and Blanc 2009;Casanueva-Reguart 2013;Li and Xu 2004;Mariscal 2004). We remain agnostic about the net effect and add these binary variables ("monopoly") to control for this influence.…”
Section: Data and Empirical Analysesmentioning
confidence: 99%
“…Emphasizing the prevalence of distinct geographies of regulation, Dowdle (2011) delineates different regulatory logics and capacities in developing countries. Studies on cases and regions explore the impact of numerous factors on agency independence, such as presidential versus parliamentary systems (Jordana & Ramio 2010); political institutions and policy context (Mariscal 2008); legal context and the judiciary (Thiruvengadam & Joshi 2012; Donaldson & Kingsbury 2013); the bureaucracy (Özel 2012; Prado 2013); and sector and country‐level institutional characteristics (Jordana et al 2011; Dubash & Morgan 2013; Dowdle 2013; Hsueh 2013; Jordana 2013). Broader frameworks, including political and economic institutions, are increasingly incorporated into regulatory analyses, echoing the canonical studies on the links between political institutions and economic outcomes.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Changes in the role of the state in telecommunications are not new. Several authors have shown that these variations are the result of changes in macroeconomic conditions and the prevailing consensus about the role of government in the economy (Vietor, 1994; Mariscal, 2002; Cowhey and Aronson, 2009; Bauer, 2010). The policy cycle designed to promote industry deregulation and the privatization of state operators which began in Latin America in the late 1980s was showing clear signs of losing momentum by the mid 2000s.…”
Section: Context Matters: Explaining Goals and Motivations In National Broadband Plansmentioning
confidence: 99%